Walking in a Patient’s Shoes: An Evaluation Study of Immersive Learning Using a Digital Training Intervention - Halton, Candida; Cartwright, Tina (Frontiers in Psychology, 2018)
Objectives: Evidence suggests that immersive learning increases empathy and understanding of the patient experience of illness. This study evaluated a digital training intervention ‘In Their Shoes’ which immerses participants in the experience of living with inflammatory bowel disease (IBD), highlighting the biopsychosocial impact. The simulation program uses a mobile application to deliver time-based tasks and challenges over 36 h, supplemented with telephone role-play and ‘kit’ items to open and use. This study investigated changes in IBD understanding and connection to patients, empathy and perception of job value in a group of pharmaceutical employees. Additionally, it explored experiences and impact of taking part in the intervention. Methods: A mixed methods pre–post design was utilized, with an opportunity sample of employees taking part in the training. 104 participants from sites in 12 countries completed measures at baseline and 97 post-intervention. Measures included the Toronto Empathy Questionnaire, Prosocial Job Characteristics Scale, and structured questions around IBD understanding and connection to patients. Two focus groups (N = 14) were conducted regarding participants experiences of the intervention to complement an open-response question in the questionnaire (N = 75). Qualitative data was analyzed using thematic analysis. Results: Following the intervention, there were statistically significant increases in IBD understanding and connection to patients (p < 0.00025), evaluation of organizational innovation (p < 0.00025), empathy (d = 0.45) and prosocial job perceptions (d = 0.28). Qualitative analysis revealed more fully the transformative personal journey undertaken by participants which provided ‘eye opening’ insight into the psychosocial impact of living and working with IBD. This insight encouraged patient perspective-taking and a strong desire to promote patient advocacy and reduce stigma around chronic illness. Finally, greater organizational pride and connectivity was evident for some participants. Conclusions: An immersive training program, focussing on the lived experience of illness, led to significant increases in disease understanding and empathy. These findings align with other literature evaluating immersive learning and the potential for increasing knowledge, empathy and motivation. The present study offers opportunities to extend this outside of the body of work focussing on healthcare practitioners and explores the benefits of using this type of learning experience within an organizational setting.